Acción de la simvastatina en la contracción de músculo liso de anillo traqueal inducida por estímulo químico y térmico - Rodríguez Lastra, Jesús (2010)
The tracheal smooth muscle contraction is associated with a significant entry of Ca2+ into the cell and depletion of intracellular stores. Simvastatin, relaxes the basilar artery by decreasing intracellular Ca2 +. The objective was to study the effect of simvastatin on smooth muscle contraction of isolated rat trachea before and after being stimulated with acetylcholine and cold water. 8 rats were anesthetized with sodium tiobarbital 60 mg/kg ip, to remove the windpipe and cut the rings, were stimulated with 10-3 M acetylcholine and cold water 18 º C with and without simvastatin. The measurements were made by ImageTool ® V. 3.0 (UTHSCSA). The arithmetic mean diameter of the tracheal muscle incubation without simvastatin significantly decreased for the stimulation of acetylcholine and cold water (p = 0.000 and p = 0.046) respectively, by adding simvastatin is tracheal diameter decreased with the stimulus of cold water which is statistically significant (p = 0.002) while that for acetylcholine is not statistically significant (p = 0.084). The mean speeds of contraction of the trachea by incubating acetylcholine/simvastatin and cold water/simvastatin, were not statistically significant (p = 0.082797 p = 0.797599). We conclude that tracheal diameter is reduced by stimulating the trachea with cold water and acetylcholine. Adding simvastatin and cold water, the effect constrictor and decreased tracheal diameter as using other calcium entry pathways that are independent of cholesterol.